Applied sociology for social work - Ingleby, Ewan (London : SAGE, 2018)
Sociology can help students understand why and how so many of the problems their service users face occur in the first place, helping them choose effective ways to communicate and make informed decisions on how their needs can be fully met. This book offers students a framework to explore how their professional responsibility to understanding sociology can be realised in every aspect of their work with a diverse range of service user groups including children and families, adults, older people, people with learning disabilities and people suffering from mental distress.
Includes bibliographical references (pages 137-140) and index.
Keywords: Social service; Sociology